Attitude and awareness towards organ donation in western India. (6th February 2015) - Balwani, Manish R.; Gumber, Manoj R.; Shah, Pankaj R.; Kute, Vivek B.; Patel, Himanshu V.; Engineer, Divyesh P.; Gera, Dinesh N.; Godhani, Umesh; Shah, Mehin; Trivedi, Hargovind L.
Abstract: Background : To determine the knowledge, attitudes and practices regarding organ donation in western India. Methods : Convenience sampling was used to generate a sample of 250; 200 interviews were successfully completed and used for analysis. Data collection was carried out via face to face interviews based on a pre-tested questionnaire in selected public areas of Ahmedabad, Gujarat state of India. Data entry was made in excel software in codes and analysis was done by SPSS software. Results : About 86% of participants were aware of the term organ donation but knowledge about its various aspects was low. About 48% aware people heard about organ donation through medical fraternity, whereas only about 21% became aware through mass media. About 59% of aware people believed there is a potential danger of donated organs being misused, abused or misappropriated. About 47% of aware people said they would consider donating organs, while only 16% said they would definitely donate irrespective of circumstances. Around 97.67% participants said they would prefer to donate to nonsmokers. About 74.41% participants were unaware about any legislation regarding organ donation. About 77% participants showed their will to donate to mentally sound persons, and 42.04% participants showed their will to donate even physically challenged people. Around 78 participants felt that they would donate organs to persons irrespective of their religion. About 81% of aware people were of the opinion that consent for organ donation after death should be given by family members. None of the interviewed participants had a donor card. Conclusion : Better knowledge and awareness will help in promoting organ donation. Effective campaign needs to be driven to educate people with relevant information with the involvement of media, doctors and religious scholars.